Experimental investigation of the applicability of a 250 kW ceria receiver/reactor for solar thermochemical hydrogen generation. (October 2022) - Thanda, V.K.; Fend, Th.; Laaber, D.; Lidor, A.; von Storch, H.; Säck, J.P.; Hertel, J.; Lampe, J.; Menz, S.; Piesche, G.; Berger, S.; Lorentzou, S.; et al.
Abstract: Solar thermochemical water splitting via a two-stage redox cycle has been subjected to numerous theoretical and experimental studies since a couple of decades. It has been considered as a promising technology to generate green hydrogen as it is feasible to directly convert concentrated solar radiation into storable chemical energy. The present article describes the results of an experimental campaign, which has been carried out to further demonstrate the feasibility of this technology. Based on the prior experience from solar gas turbine projects, a combined receiver/reactor has been designed and built up operating at temperatures between 1400 °C and 1000 °C using radiative power of up to 150 kW generated by a large-scale solar simulator (Synlight). The reactor has a total volume of 90 L with open porous ceramic foam structure. Additionally, high-performance heat exchangers have been used to recover the heat content of the product gases. Typical necessary durations for the sub-cycles, reduction and oxidation as well as durations for the corresponding necessary heating and cooling phases have been determined. By producing up to 8, 8 g of hydrogen per cycle it could be shown that the production of hydrogen in a medium scale structured reactor is possible. Graphical abstract: Image 1